OBSERVATIONS OF CATACLYSMIC VARIABLES AT KOLONICA OBSERVATORY - Parimucha, S.; Dubovsky, P.; Kudzej, I. (Одеські астрономічні публікації, 2007)
We present a small sample of our observations of cataclysmic variable stars obtained at Kolonica Observatory, The presented data for CI UMa, MR UMa and SW UM were obtained in 2006 and 2007. Our observations demonstrate that also the small telescopes with low cost CCD camera could be used for a serious and useful observations.